Impact of squamous and/or glandular differentiation on recurrence and progression following transurethral resection for non-muscle invasive urothelial carcinoma of bladder - Xu, Hao (Oncol Lett, 2017)
The aim of the present study was to investigate the impact of squamous and/or glandular differentiation on the recurrence and progression in patients with nonmuscle invasive urothelial carcinoma of bladder (NMIUCB) following transurethral resection (TURBT). A total of 869 patients with NMIUCB who had been treated with TURBT at The Second Hospital of Tianjin Medical University (Tianjin, China) between January 2006 and January 2011 were retrospectively selected for the present analysis. Associations among squamous and/or glandular differentiation with other clinical and pathological features were assessed by the χ2 test. Recurrence-free survival (RFS) and progression-free survival (PFS) curves were estimated using the Kaplan-Meier method. Univariate and multivariate analyses were performed through a Cox's proportional hazards regression model. Among the 869 patients, 232 (26.7%) patients had squamous and/or glandular differentiation. High grade tumors were more common in patients with squamous and/or glandular differentiation compared with those with pure urothelial carcinoma of bladder (P<0.001). Associations between age (P=0.115), sex (P=0.184), tumor size (P=0.223), tumor multiplicity (P=0.108), pathological tumor stage (P=0.909) and squamous and/or glandular differentiation were not observed to be statistically significant. There was a significant tendency towards higher recurrence rate and shorter RFS time in patients with squamous and/or glandular differentiation. However, no statistically significant differences were observed in progression rate and PFS between the two groups. The multivariate Cox regression analysis, identified squamous and/or glandular differentiation as an independent prognostic predictor of recurrence (hazard ratio =1.46, 95% confidence interval=1.10–1.92, P=0.008). In the present study, the presence of squamous and/or glandular differentiation was associated with a higher recurrence rate and shorter RFS time in patients with NMIUCB. Squamous and/or glandular differentiation is therefore an independent prognostic predictor of recurrence.